Global crises and populism: the role of Eurozone institutions. (3rd January 2019) - Guiso, Luigi; Herrera, Helios; Morelli, Massimo; Sonno, Tommaso
SUMMARY: Populist parties are likely to gain consensus when mainstream parties and status quo institutions fail to manage the shocks faced by their economies. Institutional constraints, which limit the possible actions in the face of shocks, result in poorer performance and frustration among voters who turn to populist movements. We rely on this logic to explain the different support of populist parties among European countries in response to the globalization shock and to the 2008–11 financial and sovereign debt crisis. We predict a greater success of populist parties in response to these shocks in Eurozone (EZ) countries, and our empirical analysis confirms this prediction. This is consistent with voters' frustration for the greater inability of the EZ governments to react to difficult-to-manage globalization shocks and financial crises. Our evidence has implications for the speed of construction of political unions. A slow, staged process of political unification can expose the European Union to a risk of political backlash if hard to manage shocks hit the economies during the integration process.